Associated Factors for Non-Ischemic Serum Myoglobin Release After Cardiac Surgical Procedures - Arndt-H, Kiessling; Florian, Grohmann; A, Stock Ulrich; Andres, Beiras-Fernandez; Angela, Kornberger; Anton, Moritz (The Heart Surgery Forum, 2014)
Background: Myoglobin has become established as a serum marker of myocardial injury. However, myoglobin levels can increase exponentially without any correlation to postoperative clinical ischemia symptoms. In this retrospective study, we analyzed the associated factors for a non-ischemic myoglobin release. Methods: We performed a data analysis from 532 consecutive cardiac surgery patients (2010 to 2011, 73% males; age 65 ± 11 years). Non-ischemic myoglobin elevation was defined as CK-MB <50 U/l and/or the absence of any ischemic clinical events (eg, myocardial infarction, mesenteric vascular occlusion). Results: Using a multifactorial model, predictive elements and associated factors for non-ischemic myoglobin increase were male sex, ejection fraction < 30%, BMI > 30 and transfusions. Serum myoglobin was not significantly different in patients with high muscle mass. Conclusions: A non-ischemic serum myoglobin release is rare, but could be associated in subgroups of patients. Further investigations should focus on clinical targets, for example, concomitant medications for which our study was not powered.